Are sternum fractures really indicative of severe trauma? (Annals of Medical Research, 2021)
Aim: To investigate the need for echocardiography in cases of sternum fracture through a retrospective analysis of the data of patients treated for post-traumatic sternal fracture. Although sternum fractures are known to be an indicator of the severity of trauma and cardiac injury, it should be evaluated whether this is always the case or whether sternum fractures could be considered benign traumas.Material and Methods: Data of 63 patients admitted to the emergency department after trauma and treated for sternum fracture between August 2014 and October 2016 were retrospectively analyzed.Results: Of the patients, 29 (46%) were female and 34 (54%) male. The mean age was 54.4±21.9 (14-89) years. Chest pain was the most common complaint among these patients admitted to the emergency department. All patients had blunt thoracic trauma. The most common injuries concomitant of sternum fractures were rib fractures. While electrocardiography and echocardiography were performed in all patients on admission to the emergency department, pericardial effusion was detected in only 1 patient by Echo. There was no significant relationship between the type of trauma exposure and the region of fracture in the sternum. All patients were treated conservatively with close follow-up for sternal fracture.Conclusion: We suggest that routine echocardiography may be unnecessary if there are no anomalies in electrocardiography findings, no cardiac marker positivity is detected and no displaced fractures are present in the computed tomography of the thorax in patients admitted to the emergency department after traum.